Gestão da satisfação e fidelidade do cliente : um estudo dos fatores que influenciam na satisfação e fidelidade dos clientes corporativos de telefonia celular - Baginski Neto, Luiz Carlos (2009)
The competition in the telecommunications industry has grown in Brazil since the privatization, forcing companies that are active in the market to a growing commitment to quality products and services in order to survive. In this context, this work aims to understand the main factors that influence the degree of satisfaction exists in respect of a mobile operator with its corporate customers. The research covered theoretical concepts and analytical models of quality management system and models of indices related to the measurement of customer satisfaction. For the field research was carried out in a practical application of the main approaches based on this thesis by a case study in corporate segment, through a questionnaire applied to 10 consultants and 40 corporate customers of that company. Comparing the results of research with the consultants and corporate clients there is the concern of respondents to the indicators that comprise the constructs of customer satisfaction, commitment calculated, the price index and the handling of complaints, denoting the dissatisfaction of the general assessment for corporate customers with the carrier, against its current expectations. It is concluded that the mobile operator of the telecommunications industry have a big challenge, after ten years of privatization and consequently the period of rapid expansion of customer base and with the depleted, retain corporate customers as highly strategic, thus avoiding that migrate to other companies. We emphasize the need for further research and analysis of different approaches through research and using the same models to specifically evaluate and measure customer satisfaction of mobile enterprise, to adjust the model to the national market. Finally, we suggest the creation of an effective customer loyalty program with a strategy of relationship and specific to the corporate sector of mobile telephony